Effects of Finaplix® Synovex-S®, and Ralgro® implants, singularly or in combinations, on performance, carcass traits, and longissimus palatability of Holstein steers - Apple, J.K.; Simms, D.D.; Kuhl, Gerry L.; Dikeman, Michael E.; Kastner, Curtis L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Over the entire feeding period (249 d). Finaplix® (F) plus Synovex-S® (S)-implanted steers had higher (P<.05) daily gains than F+Ralgro® (R), F; and control (C) steers. All treatments produced higher (P<.05) daily gains than C. with the exception of F: The only feed efficiency differences were during the fourth implant period. when F steers were more (P<.05) efficient than F+R or C steers. The F+S and F+R steers had higher (P<.05) masculinity scores than Sand C steers. Carcasses of F +S steers were heavier (P<.05) than those of F and C steers. The F+S steers had larger (P<.05) ribeyes than R, F; and C steers. Also, F+S steers tended (P=.07) to have lower yield grades than S, R. or C steers. Even though marbling scores and quality grades were similar (P>.05) among treatments. only 50% of F+S carcasses graded low Choice or higher compared to a range of 75 to 100% for the other treatments. The only meat palatability differences were tenderness scores; steaks from Sand F + R steers were less tender (P<.07) than those from Rand C steers.
Keywords: Beef; Holsteins; Implants; Performance; Carcass traits; Meat palatability